Healthcare utilisation, induced labour and caesarean section in the pregnancy after stillbirth: a prospective study. (14th July 2017) - Gravensteen, IK; Jacobsen, E‐M; Sandset, PM; Helgadottir, LB; Rådestad, I; Sandvik, L; Ekeberg, Ø
Abstract : Objective: To investigate healthcare utilisation, induced labour and caesarean section (CS) in the pregnancy after stillbirth and assess anxiety and dread of childbirth as mediators for these outcomes. Design: Population‐based pregnancy cohort study. Setting: The Norwegian Mother and Child Cohort Study. Sample: A total of 901 pregnant women; 174 pregnant after stillbirth, 362 pregnant after live birth and 365 previously nulliparous. Methods: Data from questionnaires answered in the second and third trimesters of pregnancy and information from the Medical Birth Registry of Norway. Main outcome measures: Self‐reported assessment of antenatal care, register‐based assessment of onset and mode of delivery. Results: Women with a previous stillbirth had more frequent antenatal visits (mean 10.0; 95% CI 9.4–10.7) compared with women with a previous live birth (mean 6.0; 95% CI 5.8–6.2) and previously nulliparous women (mean 6.3; 95% CI 6.1–6.6). Induced labour and CS, elective and emergency, were also more prevalent in the stillbirth group. The adjusted odds ratio for elective CS was 2.5 (95% CI 1.3–5.0) compared with women with previous live birth and 3.7 (1.8–7.6) compared with previously nulliparous women. Anxiety was a minor mediator for the association between stillbirth and frequency of antenatal visits, whereas dread of childbirth was not a significant mediator for elective CS. Conclusions: Women pregnant after stillbirth were more ample users of healthcare services and more often had induced labour and CS. The higher frequency of antenatal visits and elective CS could not be accounted for by anxiety or dread of childbirth. Tweetable abstract: Women pregnant after stillbirth are ample users of healthcare services and interventions during childbirth. Abstract : Tweetable abstract Women pregnant after stillbirth are ample users of healthcare services and interventions during childbirth.